Mitochondria Synergize With P2 Receptors to Regulate Human T Cell Function - Ledderose, Carola; Junger, Wolfgang G. (Frontiers in Immunology, 2020)
Intracellular ATP is the universal energy carrier that fuels many cellular processes. However, immune cells can also release a portion of their ATP into the extracellular space. There, ATP activates purinergic receptors that mediate autocrine and paracrine signaling events needed for the initiation, modulation, and termination of cell functions. Mitochondria contribute to these processes by producing the ATP that cells release. Here, we summarize the synergistic interplay between mitochondria and purinergic signaling that regulates T cell functions. Specifically, we discuss how mitochondria interact with P2X1, P2X4, and P2Y11 receptors to regulate T cell metabolism, cell migration, and antigen recognition. These mitochondrial and purinergic signaling mechanisms are indispensable for host immune defense. However, these mechanisms also represent an Achilles heel that can render the host susceptible to infections and inflammatory disorders. Hypoxia and mitochondrial dysfunction deflate the purinergic signaling mechanisms that regulate T cells, while inflammation and tissue damage generate excessive systemic ATP that distorts autocrine purinergic signaling and impairs T cell function. An improved understanding of these metabolic and purinergic signaling mechanisms that regulate T cells may reveal novel strategies for the diagnosis and treatment of infectious and inflammatory complications.